FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP HASIL UJI SENSITIVITAS - Elisa Rinihapsari; Benaya Yamin Onesiforus; Sendhy Pravitadewi Ayusari; May Wulan Ayu Andani; Naomy Cahya Marinda; Anastasia Desi Risma (LPPM Universitas Abdurrab, 2025)
Antibiotic Susceptibility Testing (AST) is a fundamental element in the management of bacterial infections and in determining effective antimicrobial therapy for patients. AST methods continue to evolve; however, not all hospitals are equipped with automated testing facilities. Hence, conventional manual AST remains the primary option. This study explored the factors that may influence the results of AST by introducing variations to the reference standard procedures outlined in the CLSI guidelines. AST was conducted using the Kirby-Bauer disc diffusion method on Staphylococcus aureus and Escherichia coli bacteria. The independent variables in this study were the type of media, media thickness, incubation temperature, and incubation time. The dependent variable was the diameter of the inhibition zone around the antibiotic discs. The inhibition zone diameters were compared to the CLSI references. Statistical analysis was performed to determine whether there were significant differences in sensitivity test results across the variations for each tested variable. Based on the research results, it can be concluded that variations in the type of media (MHA, NA, and PCA), media thickness (2, 4, and 6 mm), incubation temperature (25, 35, and 45°C), and incubation time (18, 24, and 48 hours) affect the results of the AST. With these findings, it is recommended that Medical Laboratory Technology personnel continue to follow the standard procedures according to CLSI guidelines to ensure that the results and their interpretations are accountable.